Design, construction and validation of a planar probe for measuring complex relative permittivity of materials - Piladaeng, Nawarat; Angkawisittpan, Niwat; Nuan-On, Adisorn (International Journal of Engineering and Technology, 2019)
A planar probe for inspecting the complex relative permittivity of materials was redesigned and constructed in this research. The       proposed planar probe was made of the Arlon AD260A PCB with the coaxial and microstrip structure. Experiments were conducted in the frequency range of 0.5-6 GHz. Ethanol and methanol were used as samples to validate the probe. It was found that the complex   relative permittivity of the samples had a good tendency to the references in the frequency range of 0.5-2 GHz. Moreover, this redesigned probe provided improved accuracy on the measurement compared to the conventional planar probe.